Manggaraian Idea Of “Moral-Self”: Study Of Manggaraian Traditional Texts - Fransiskus Borgias (Asosiasi Ahli Filsafat Keilahian Indonesia, 2020)
Western philosophers called the idea of “individual-self” a “modern project”. Charles Taylor traced its historical development back to great philosophers of European rationalism (Kant, Hegel, Rousseau, J. G. Herder) with the birth of modern awareness of “individual-self” connected to western-modern individualistic society. Based on a study of “ethical-texts” preserved in Manggaraian oral-tradition, however, I postulate that indigenous tribes have their own way-of-thinking about individual-self, particularly individual-moral-self. Manggaraian people, though mainstream anthropology categorize it communal-traditional society, have some basic knowledge of the idea of moral-self, in the philosophical terminology of Taylor. Strong awareness of moral-self endorses people to have courage to make a personal-individual moral decision (Tillich). Traditional-ethical texts endorse individuals to have their own opinion on important issues of social-moral life, though they will different from the mainstream. Individuals do not depend upon social-communal values. Also in traditional community individuals are endorsed to make their own moral considerations though it means they contradict society. In moral issues individuals should make their own decision. This study traces such tendency in one of traditional community, Manggarai, in Flores, East Nusa Tenggara. It is based on several field research conducted in Manggarai for a project of doctoral dissertation.